University management: an approach to the strategic functioning of the dimensions: teaching, research and extension (Educational Knowledge, 2022)
This research is the result of a documentary review, whose objective was the integration of various disciplinary perspectives around university management, as the process that should guide, promote and motorize the competitive training of citizens, with the flexibility to face the challenges of a globalized and constantly changing world. In addition to making strategic decisions and becoming active agents, committed to the transfer of scientific knowledge produced at the University to the social scene, thus maximizing the conditions of well-being and quality of life.In conclusion, facing the challenges of a globalized, competitive world permeated by dynamism and progressivity, suggests strengthening interactive society-University links in which the opportunities for multidimensional growth can be diversified; and expand the inclusive possibilities as a result of the provision of knowledge at the service of solving the problems that afflict humanity.